Alkamide Content and Localization in Heliopsis longipes Cypselae, Obtained via Fluorescence and Double-Multiphoton Microscopy - Juan Vázquez-Martínez; Jorge Molina-Torres (Molecules, 2024)
The alkamide content and specific tissue localization in the cypselae of Heliopsis longipes were investigated using gas chromatography–electron ionization mass spectrometry (GC-EIMS) and multiphoton fluorescence microscopy (MPFM). GC-EIMS analysis identified two olefinic alkamides: affinin (spilanthol) and N-2-methylbutyl-2E,6Z,8E-decatrienamide. Microscopic analysis revealed that alkamides are localized within the cotyledons, and specifically compartmentalized in lipid bodies, highlighting their spatial organization. The linear unmixing of fluorescence emission fingerprints showed that affinin exhibits autofluorescence at 693 nm, corresponding to the red spectral region. This emission is attributed to the conjugated double bonds in its acyl chain. This study is the first to report on the presence and precise localization of alkamides in the cypselae of H. longipes.